Methylenetetrahydrofolate reductase gene-specific methylation and recurrent miscarriages: A Case- Control Study from North India - Kallur Nava Saraswathy; Lovejeet Kaur; Seerat Talwar; Jyoti Mishra; Suraj Huidrom; M P Sachdeva; Manju Puri (Wolters Kluwer Medknow Publications, 2018)
Aim: This study aimed to understand the association of gene-specific methylation of the promoter region of methylenetetrahydrofolate reductase (MTHFR) in the causation of recurrent miscarriages (RMs) both independently and also in light of MTHFR C677T polymorphism, hyperhomocysteinemia, folate, and Vitamin B12 deficiency. Settings and Design: This was a hospital-based, case-control, observational study. Methods: The proposed study included a total of 85 RM cases and 121 nonpregnant controls. Biochemical (homocysteine, folate, and Vitamin B12) investigations, MTHFR polymorphism (C677T), and MTHFR allele-specific methylation were done on all the samples. Results: Methylation-specific polymerase chain reaction of MTHFR gene revealed that methylated allele (single dose) was found to pose a significant 3.6-fold increased risk for RM. The degree of risk of methylated allele for RM was found to be aggravated from the normal genotype CC (2.8 folds) to CT (7.5 folds) individuals. Vitamin B12 deficiency and folate repletion were found to be posing an increased risk in association with methylated allele for recurrent miscarriages as compared to the respective controls. Conclusion: Recurrent miscarriage cases were found to be hypermethylated with respect to MTHFR gene-specific methylation as compared to the controls. High prevalence of folate repletion causing imbalance between folate and Vitamin 12 levels may lead to hypermethylation among recurrent miscarriage cases. The present study highlights the significance of the epigenetic mechanisms in the causation of the recurrent miscarriages.